Talent Management Predictors that Adversely Affect Job Satisfaction at a South African Parastatal - Patrick Lekgothoane; Molefe Maleka; Zeleke Worku (Journal of Economics and Behavioral Studies, 2018)
The purpose of the study was to quantify talent management predictors that adversely affect job satisfaction (JS). The literature review revealed that talent management predictors (i.e. neglecting experience during recruitment and appointment of managers, and supervisors’ lack of confidence in the achievement of goals) adversely affected JS. The research design was cross-sectional, pre-experimental, and a survey. Data were collected at a parastatal business unit with a population size of 800.Using calculating statistics, the appropriate sample size was n=204. The sample was stratified by gender and occupation. Data were collected by means of a validated questionnaire and analyzed by means of frequencies, and logit analysis. Bayesian analyses were used to test the hypotheses. The three hypotheses were supported; showing that employees are more likely to be dissatisfied if their experience was not considered during recruitment, if their experience was neglected when managers were appointed irrespective of their gender, and if supervisors lacked confidence that the organizational strategic goals would be achieved. Recommendations for future research are made. This study has implications for managers in the sense that if they do not factor in experience, i.e. during recruitment and appointment, they might have supervisors who do not have confidence in expressing the strategic goals of the parastatal. This study adds value to the existing body of knowledge by quantifying talent management factors using odds ratios to determine talent management predictors that adversely affect JS.